A Retrospective Analysis of the Clinical Impact of 939 Chest Radiographs Using the Medical Records. (20th December 2012) - Geijer, Mats; Ivarsson, Liz; Göthlin, Jan H.
Abstract : Objective . Between one-third and half of all radiology examinations worldwide are probably chest studies. The aim of the current study was to retrospectively evaluate the clinical influence of chest radiography. Methods . In a tertiary referral hospital, 939 consecutive daytime chest radiography examinations were evaluated. The outcome was classified as normal, incidental, or pathologic. The referring physician's reaction to radiologic outcome was classified as highly expected, moderately expected, or unexpected. The influence on the patients' treatment was divided into four groups from major to no influence. Results . In all, 71.6% of the studies had a highly expected outcome. Moderately expected or unexpected outcomes were noted in 36.6% of 500 pathologic examinations. Unexpected outcome was noted in 11.6% of all studies. The radiologic outcome influenced treatment in 65.4% of patients where pathology was demonstrated. Patients with normal or incidental findings had treatment influenced in 1/3 of the cases. Unexpected findings influenced treatment more than moderately expected findings. When radiological findings were highly expected, treatment was influenced in less than half of the cases. Surprisingly few chest radiology examinations were commented upon in the medical records.